2019
DOI: 10.1075/aplv.00004.bar
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Matukar Panau kinship terminology

Abstract: Referential kinship terms in Matukar Panau (Oceanic, Papua New Guinea) are obligatorily possessed. Traditionally, kinship terms are directly possessed in Oceanic languages (with an obligatory suffix on the root that agrees with the person and number of the possessor). In Matukar Panau, some kinship terms are also indirectly possessed (with a classifier that agrees with the person and number of the possessor). A third pattern shows double-marking of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…In sociolinguistic studies gender is often found to condition variation, though this seems to be less significant in the case of morphosyntactic variation (Meyerhoff, 2013). However, in Barth's (2019) study of the variation in the Matukar Panau kinship possession system, gender was found to be significant in driving the changes to the system. It is possible that the choice of a certain construction signals some social meaning.…”
Section: Gender Of the Speakermentioning
confidence: 92%
See 4 more Smart Citations
“…In sociolinguistic studies gender is often found to condition variation, though this seems to be less significant in the case of morphosyntactic variation (Meyerhoff, 2013). However, in Barth's (2019) study of the variation in the Matukar Panau kinship possession system, gender was found to be significant in driving the changes to the system. It is possible that the choice of a certain construction signals some social meaning.…”
Section: Gender Of the Speakermentioning
confidence: 92%
“…Speaker age was also found to be significant in Barth's (2019) study of the variation in kinship possession strategies, with younger women and older men found to be driving the shift to indirect possession strategies. We therefore investigate whether the same pattern holds for the variation in directional constructions.…”
Section: Speaker Agementioning
confidence: 95%
See 3 more Smart Citations